PHENOMENOLOGICAL ETHICS IN A MULTI-RELIGIOUS SOCIETY: Nigeria as a Case Study - Nicholas Onyemechi Alumona; Grace Ogelenya (Journal of Dharma, 2024)
Multi-religious societies are prone to conflicts because of several factors that create room for divisiveness. Nigeria has been witnessing religious conflicts, especially between Muslims and Christians. It consequently appears as if religious conflicts in Nigeria and other multi-religious societies have defied the logic of conflict resolution. This breeds the problem of entrenching peace among religions with seemingly opposing doctrines and varying perceptions of the Supreme Being. Employing the methods of analysis and phenomenology, this essay argues that phenomenological ethics as a presuppositionless method of determining what is right or wrong is a better approach of not only resolving conflicts but also preventing them. It concludes by positing that a comprehensive teaching of phenomenological ethics in different religions can translate the method into an attitude which inculcates in one’s psyche oneness as the ultimate goal of every religion, culminating in peaceful co-existence.